2017
DOI: 10.2495/cmem-v6-n3-499-514
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion propagation phase and bond strength degradation of reinforced concrete structures: State of the art

Abstract: Corrosion causes damage to reinforcing steel in concrete structures and governs the service life of the structures. Currently, researchers are paying attention to modelling the behaviour of the bond between the concrete and steel interface of corroded reinforcement. The main objective of this paper is to study the recent research relevant to the bond behaviour at the interface between corroded ribbed bars and concrete and to identify the future research focus. Initially, the paper presents the mechanisms of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In fact, a study by Silva et al [2] for recycled concrete aggregates (RCA) concrete concluded that, for a simply supported beam (rectangular cross-section), the strength of concrete affects the cross-section of the beam (Equation (1)). Similar facts can be true for cost and durability of the concrete mixes in which the thickness of the concrete cover is affected by its durability characteristics [3].…”
Section: Introductionsupporting
confidence: 59%
“…In fact, a study by Silva et al [2] for recycled concrete aggregates (RCA) concrete concluded that, for a simply supported beam (rectangular cross-section), the strength of concrete affects the cross-section of the beam (Equation (1)). Similar facts can be true for cost and durability of the concrete mixes in which the thickness of the concrete cover is affected by its durability characteristics [3].…”
Section: Introductionsupporting
confidence: 59%